Comparison of smartphone based peek visual acuity with Snellen Visual Acuity - Dulani, Nisha; Dulani, Harish; De, Tapas Kumar (Creative Pharma Assent, 2023)
Purpose: To test an alternative method of visual acuity assessment by comparing habitual and best-corrected visual acuity by Snellen and Peek (a visual acuity testing smartphone application). Methods: A prospective study comparing visual acuity using Snellen's and Peek's visual acuity charts (smartphone-based applications). 162 eyes were assessed in this hospital-based setting by a single observer. Patients with gross ocular pathology and visual acuity less than 6/60 were excluded from the study. Results: There was no statistically significant difference between best corrected visual acuity by Snellens and Peeks'. Snellen's mean best corrected visual acuity was 0.9902 (±0.075), and Peek acuity was 0.9875 (±0.080). Conclusion: The visual acuity assessment by Peek is comparable to that of Snellen's; hence, it can be used as an excellent alternative to Snellens' visual acuity testing.